A multilayered regulatory mechanism for the autoinhibition and activation of a plant CC‐NB‐LRR resistance protein with an extra N‐terminal domain. Issue 1 (12th May 2016) - Chen, Xiaojiao; Zhu, Min; Jiang, Lei; Zhao, Wenyang; Li, Jia; Wu, Jianyan; Li, Chun; Bai, Baohui; Lu, Gang; Chen, Hongyu; Moffett, Peter; Tao, Xiaorong
Summary: The tomato resistance protein Sw‐5b differs from the classical coiled‐coil nucleotide‐binding leucine‐rich repeat (CC‐NB‐LRR) resistance proteins by having an extra N‐terminal domain (NTD). To understand how NTD, CC and NB‐LRR regulate autoinhibition and activation of Sw‐5b, we dissected the function(s) of each domain. When viral elicitor was absent, Sw‐5b LRR suppressed the central NB‐ARC to maintain autoinhibition of the NB‐LRR segment. The CC and NTD domains independently and additively enhanced the autoinhibition of NB‐LRR. When viral elicitor was present, the NB‐LRR segment of Sw‐5b was specifically activated to trigger a hypersensitive response. Surprisingly, Sw‐5b CC suppressed the activation of NB‐LRR, whereas the extra NTD of Sw‐5b became a positive regulator and fully activated the resistance protein, probably by relieving the inhibitory effects of the CC. In infection assays of transgenic plants, the NB‐LRR segment alone was insufficient to confer resistance against Tomato spotted wilt tospovirus ; the layers of NTD and CC regulation on NB‐LRR were required for Sw‐5b to confer resistance. Based on these findings, we propose that, to counter the negative regulation of the CC on NB‐LRR, Sw‐5b evolved an extra NTD to coordinate with the CC, thus developing a multilayered regulatory mechanism to control autoinhibition and activation.